The Role of Velocity Based Training in the Strength Periodization for Modern Athletes - Guerriero, Aristide (J Funct Morphol Kinesiol, 2018)
Resistance training (RT) is considered the most important method to improve the athlete’s strength and rate of force development (RFD). In the last decade, the importance of monitoring velocity during RT has drastically grown, because of an increased availability of linear position transducers (LPT) and inertial measurement units (IMU). The purpose of this review is to analyze the existing literature on testing techniques and performance strategies used to enhance strength and power performance of elite athletes, by monitoring the velocity of resistance training. The authors focus in particular on the level of effort of resistance training defined by velocity; how the loss of velocity correlates with the degree of fatigue and how it can be used to enhance the performance of competitive athletes; the use of LPT as part of the daily routine of the strength and conditioning programs in competitive sport. It is therefore critical for the sports scientists to have a correct understanding of the basic concepts of the velocity-based training and their application to elite sports. The ultimate goal is to give some indications on the velocity-based resistance training integration in the programs of different sports in the high performance environment.